Arabic Teaching Methods for Non-Native Speakers: Types, Advantages, and its Application in Indonesia - Sangidu Sangidu (International Islamic Schools Alliance, 2021)
The problem of learning Arabic for non-native speakers in Indonesia is influenced by two factors; linguistic factors and non-linguistic factors. Linguistic factors include phonology, morphology, syntactic, and vocabulary. Meanwhile, non-linguistic factors include social, culture, motivation, methods, learning environment and so forth. This paper discusses the problems of learning Arabic for non-native speakers in Indonesia, the types of methods, its advantages, and its application. The results of the study conclude that Islamic boarding schools, Islamic schools, and campuses that carry out Arabic lessons need to provide native speakers from Arab countries or send students to Arab countries.